PENGARUH INFLASI, SUKU BUNGA DAN NILAI TUKAR TERHADAP HARGA SAHAM - Ependi Ependi (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This study aims to analyze the effect of inflation, interest rates and exchange rates on consumer goods company stock prices, either partially or simultaneously. This Researh using quantitative data and time series data obtained from financial statements PT. Siantar Top Tbk. The sampling technique used was purposive sampling taken during the period 2017-2020 Stock Prices, Inflation, Interest Rate and Exchange Rate. Analysis model used in this study was a multiple linear regression analysis. The results of this study indicate partial variable inflation rate has a significant negative correlation effect and variable interest rate has positively and significantly correlated to the price of company stock Siantar Top Tbk. Exchange Rates does not have a significant effect on stock price fluctuations Siantar Top. While the simultaneous or independent variable inflation rate, interest rate and exchange rate has a significant influence on company's stock price Siantar Top. The coefficient of determination in this study was 71.29%, which indicates that the variation in inflation, Interest Rate, and Exchange Rate was able to explain the variation in stock price PT. Siantar Top Tbk. While the remaining 28.71% is explained variables other variables